2015
DOI: 10.3109/0886022x.2015.1012983
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endogenous hydrogen sulfide on toll-like receptor pathway in renal ischemia/reperfusion injury in rats

Abstract: In this study, we investigated the impact of endogenous hydrogen sulfide (H 2 S) on toll-like receptors (TLRs)-mediated inflammatory response and apoptosis in renal ischemia-reperfusion injury (IRI). Twenty-four male Wistar rats were randomly divided into four groups: sham, IR, IR + propargylglycine (PAG) and IR + hydroxylamine (HA). After right nephrectomy, rats were given saline for the sham and IR group, PAG for the IR + PAG group and HA for the IR + HA group, through the left renal artery for 20 min. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…5 . This finding is in line with previous studies 32 33 34 35 36 37 which showed that upregulation of expression of cytokines or activation of NF-κB in glomeruli, renal tubules, and the peritubular interstitium were detected during the acute kidney injury induced by ischemia reperfusion injury. These suggest that interstitial cells (such as morphologies, resident leukocytes/monocytes) may also play an important role in the acute kidney injury, which deserved further study.…”
Section: Discussionsupporting
confidence: 92%
“…5 . This finding is in line with previous studies 32 33 34 35 36 37 which showed that upregulation of expression of cytokines or activation of NF-κB in glomeruli, renal tubules, and the peritubular interstitium were detected during the acute kidney injury induced by ischemia reperfusion injury. These suggest that interstitial cells (such as morphologies, resident leukocytes/monocytes) may also play an important role in the acute kidney injury, which deserved further study.…”
Section: Discussionsupporting
confidence: 92%
“…Shibuya et al [ 15 ] demonstrated that H 2 S suppressed high glucose-induced cardiomyocyte inflammation by inhibiting the TLR4/NF- κ B pathway and NLRP3 activation. Moreover, Tan et al [ 35 ] also identified the protective effect of endogenous H 2 S on renal IRI by suppressing inflammatory response through the inhibition of the TLR pathway. Zhang et al [ 19 ] demonstrated that H 2 S could attenuate LPS-induced acute lung injury by reducing oxidative stress and inhibiting inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…DNA fragmentation, an apoptotic marker, within cells fixed in the thin sections of liver was detected in situ (TACS•XL DAB In Situ Apoptosis Detection Kit, Trevigen Inc., Gaithersburg, MD). Terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL)-positive cells were counted under high power microscopy on 10 non-overlapping areas in each case and are presented as percent positive cells per total number of cells counted in the field [ 70 ].…”
Section: Methodsmentioning
confidence: 99%